IMPLEMENTATION OF PROBLEM-BASEDLEARNING TECHNOLOGY IN TEACHING DIFFERENTIAL EQUATIONS - Khalikov Suyunjon Hamrokul ogli (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article provides examples and suggestions for the use of problem-based learning technology in problem-solving differential equations. There are also experiments to determine its level of effectiveness.